The Influence of Organizational Commitment on the Performance of Employees of PT Angkasa Pura II Husein Sastranegara International Airport Branch Bandung, West Java - Aridhita Eltia Anggraeni; Kifni Yudianto (CV. Rayyan Dwi Bharata, 2023)
Actions that show the level of commitment of an individual to the organization in which he or she works are known as organizational commitment. A work attitude that pays attention to their responsibilities, is very responsible in carrying them out, and is very loyal to the organization is a sign of commitment to the organization. At PT Angkasa Pura II Husein Sastranegara International Airport branch in Bandung, West Java, the purpose of this study was to determine the partial effect and how much influence organizational commitment has on employee performance. This study uses a quantitative approach, with primary and secondary data as the type of data used. A survey using a questionnaire was used as a data collection method. All employees are used as a population, namely as many as 126 people. For the selection of samples used simple random sampling method, namely as many as 100 people. With a tcount of 6,650 1,984 and a significance level of 0.000 0.05, the H1 hypothesis can be accepted because the variable organizational commitment has a positive and significant effect on employee performance. However, an R2 value of 0.311 or 31.1% was obtained which indicates that organizational commitment has a weak relationship with employee performance. The remaining 68.9% is caused by other factors that are not the subject of this study.